2019
DOI: 10.1177/0003319718822348
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Characteristics of Mismatch Lesions: An Angiographic and Intravascular Ultrasound Analysis of 1369 Coronary Lesions

Abstract: Objectives:To evaluate the angiographic and intravascular ultrasound (IVUS) characteristics of coronary mismatch lesions.Background:Better understanding about the characteristics of mismatch lesions may help to achieve more accurate lesion assessment and, thereby, to improve the outcomes of percutaneous coronary intervention (PCI).Methods:Angiographic and IVUS data from 1369 lesions were analyzed. Mismatch lesion was defined as the difference between proximal and distal reference lumen diameters of ≥1.0 mm or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…9 The geometrical effects on a lower FFR were supported by the computational simulation. 9 The multiple local geometric factors involved in CAD lesions appear to play a significant role in the significance of MCL as reported by Phan et al 1…”
Section: Local Cad Geometric Factors MCL Ffr and Lesion Instabilitymentioning
confidence: 79%
See 4 more Smart Citations
“…9 The geometrical effects on a lower FFR were supported by the computational simulation. 9 The multiple local geometric factors involved in CAD lesions appear to play a significant role in the significance of MCL as reported by Phan et al 1…”
Section: Local Cad Geometric Factors MCL Ffr and Lesion Instabilitymentioning
confidence: 79%
“…In their article on the angiographic and intravascular ultrasound (IVUS) imaging characteristics of mismatch coronary lesions (MCLs), Phan et al emphasize how common MCLs are and how these lesions offer many challenging characteristics for the interventionalist performing a percutaneous coronary intervention (PCI). 1 The definition of MCL is a coronary artery lesion that has a significant difference in plaque burden between the distal and proximal segments. The authors found, by coronary angiography (CAG), a 24.1% incidence of mismatch lesions (411/1706 lesions) and reported that the mismatch lesions were longer than non-mismatch lesions (22.1 + 6.6 mm vs 18.7 + 6.4 mm, respectively; P < .001) and that they also had a smaller minimum lumen diameter by CAG (0.66 + 0.44 vs 0.98 + 0.45, respectively; P < .001).…”
mentioning
confidence: 99%
See 3 more Smart Citations